Pomiar potrzeb medycznych - dylematy metodyczne - Hołub-Iwan, Joanna (Errors of the Measurement of Medical Needs, 2006)
An indication of areas which are causing errors is the purpose of the article in the measurement of medical needs for society as well as to be the attempt at returning the remark that pointed variables or variables resulting from presented factors should taken into consideration in the process of analysing and predicting medical needs. The author is showing how the pretermission of the specificity of medical needs is able to influence their quality of the measurement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 597-604